Digital image analysis using video microscopy of human-derived prostate cancer vs normal prostate organoids to assess migratory behavior on extracellular matrix proteins - Marr, Kendra D.; Ignatenko, Natalia A.; Warfel, Noel A.; Batai, Ken; Cress, Anne E.; Pollock, Grant R.; Wong, Ava C.; Lee, Benjamin R. (Frontiers in Oncology, 2023)
The advent of perpetuating living organoids derived from patient tissue is a promising avenue for cancer research but is limited by difficulties with precise characterization. In this brief communication, we demonstrate via time-lapse imaging distinct phenotypes of prostate organoids derived from patient material– without confirmation of cellular identity. We show that organoids derived from histologically normal tissue more readily spread on a physiologic extracellular matrix (ECM) than on pathologic ECM (p<0.0001), while tumor-derived organoids spread equally on either substrate (p=0.2406). This study is an important proof-of-concept to defer precise characterization of organoids and still glean information into disease pathology.